Biophysical effect of climate change on summer crops - Confalone, Adriana E.; Vilatte, C. A.; Aguas, Laura M.; Barufaldi, Monica F.; Eseiza, M. F.; Ponce, Griselda D. (Cuban Journal of Agricultural Science, 2017)
The effect of climate change on yield of soybean and maize crops was determined in Azul, Buenos Aires, Argentina. DSSAT crop models, previously calibrated, were used, under local conditions. Projections of PRECIS regional climate model in the SRESA2 stage were used, for the decades 2020-29 and 2050-59, in order to obtain potential yields. Later, the effect of heat waves during the growth cycle 2013-14 was evaluated. Climate projections indicated an increase of yields of crops during dryland farming crops. In soybean (Glycine max (L.) Merr.), the increase was 25 and 28 %, and in maize (Zea mays), it was 19 % and 26 %, for the decades 2020-29 and 2050-59, respectively. However, considering thermal variability imposed by the heat wave, it was evident that soybean and maize showed a reduction of yield when they are sown without irrigation during those extreme events. Yield decreases reach 19 % in soybean and 36 % in maize. Comparing yields of crops irrigated in a year considered as typical with respect of the year of heat wave, the increase of temperature benefits maize with a 22 % of yield increase, but harms soybean with a decrease of 13 %. Influence of temperature increase, together with water deficiencies, produces different effects on C3 species like soybean, and in C4 like maize. It is suggested to develop more research on the effects of extreme phenomena on different phenological phases of crops so the sustainability of agroecosystems from the center of Buenos Aires province could be mantained. Key words: food safety, heat wave, soybean, maize